(untitled) (Research, Society and Development, 2020)
The aim of this study is to identify the main contemporary trends of research in Environmental Education, to verify their gaps in interdisciplinary and holistic teaching in Brazil. To this end, a complete reading of articles from five national scientific journals with environmental focus, published between 2013 and 2016 and evaluated as B1 in Qualis (Capes) in the Teaching area, was performed. The data found were categorized into: percentage of publications per journal, thematic focuses, geographical distribution, educational institutions involved, educational levels, educational modalities and disciplines involved in the insertion of sustainable didactic strategies. The spheres of biology and science stood out for research in this area. Note the disparity in the concentration of regional studies, where the South and Southeast regions revealed high publications to the detriment of the Midwest region, as well as the modest amount of research on didactic and inclusive methodologies, climate change, basic sanitation and recognition. human being as an inherent element of the environment. This scenario delimits the barriers of interdisciplinary education in Brazil, whose legislation elucidates the need to employ critical environmental education in pedagogical curricula at all levels of education, aiming to establish a strategy-forming base in accordance with sustainable development.